Aik Nyet Sesaot's Tourism Development Strategy Using SWOT Analysis and Pls-Sem Approach - Yusril Hayadi; Muhammad Dzul Fadlli (International Journal of Economics, Business and Innovation Research, 2024)
Aik Nyet is one of the tourist areas in Sesaot Village, Narmada District, West Lombok Regency, which presents a natural scenery with rivers, springs, and protected forests that are still very beautiful. The existence of this Aik Nyet Sesaot tourist area has a significant positive impact on the social and economic of the community. This positive impact is a strong foundation for tourism managers, village governments, and local governments to increase the development of aik nyet tourism in a better and more sustainable direction. This study aims to find out the development strategy of aik nyet tourism in the Sesaot area using SWOT analysis and the Pls-sem approach. This study uses a quantitative research method with data collection by distributing questionnaires and conducting data analysis using SWOT analysis and Partial Least Square-Structural Equation Modelling (PLS-SEM). The results of the study showed the average percentage of respondents' answers, which were then mapped into instruments in determining SWOT (Strengths, Weaknesses, Opportunities, and Threats). In addition, the test results using PLS-sem also show that the accessibility of tourism in the Aik nyet Sesaot tourist area has a positive and significant value when viewed from the calculation results, which show a < value of 0.05, namely 0.007 < 0.05. The cost was also positive and significant, with a result of 0.037< 0.05. Furthermore, the environmental impact was negative and insignificant, with a result of -0.098 > 0.05. Attractiveness has a positive and significant value with a result of 0.139 < 0.05. Supporting facilities have negative and insignificant values with results of -0.005 > 0.05. Finally, popularity has positive and significant values with results of 0.259 < 0.05.